2021
DOI: 10.1002/mma.7480
|View full text |Cite
|
Sign up to set email alerts
|

A new representation of the extended k‐gamma function with applications

Abstract: In this study, a new series representation of the extended k‐gamma function is investigated. A new representation expresses this function as an infinite sum of delta functions. Several researchers have examined this family of functions, but no study has been conducted dealing with the fractional kinetic equation. A new representation proves useful to solve the fractional kinetic equation involving an extended k‐gamma function. Particular cases involving the original gamma function are discussed as corollaries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…The interested reader is directed to [29][30][31][32][33] and associated references therein for a more extensive and exhaustive review of related work. In recent years, Tassaddiq [34] has investigated a distributional representation of the extended k-gamma function in terms of complex delta function as follows:…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The interested reader is directed to [29][30][31][32][33] and associated references therein for a more extensive and exhaustive review of related work. In recent years, Tassaddiq [34] has investigated a distributional representation of the extended k-gamma function in terms of complex delta function as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its action on a suitably chosen function over a specific domain is easily obtainable by means of the standard techniques applied to delta function, and it is found that [34] 2…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations